2017
DOI: 10.18671/scifor.v45n116.12
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for regulating timber volume in forest stands

Abstract: ResumoOs objetivos desta pesquisa foram: 1) avaliar duas estratégias de otimização para minimizar a diferença entre a máxima e mínima produção anual e minimizar os desvios de produção entre anos consecutivos; 2) comparar a sua performance com dois modelos tradicionais para regular o fluxo de volume de madeira. O problema deste estudo representou a situação real de uma empresa localizada no estado de Santa Catarina, Brasil, onde a estrutura da floresta estava altamente irregular, devido ao predomínio de povoame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
1
2
0
1
Order By: Relevance
“…In a previous work to the present study, Fiorentin et al (2017) found that negative net revenue values were found in all formulated optimization strategies in the planning horizon periods where the number of areas subjected to the first thinning was high. The authors attributed these results to the low economic value of pulpwood and the high harvest values associated with the first and second thinning.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In a previous work to the present study, Fiorentin et al (2017) found that negative net revenue values were found in all formulated optimization strategies in the planning horizon periods where the number of areas subjected to the first thinning was high. The authors attributed these results to the low economic value of pulpwood and the high harvest values associated with the first and second thinning.…”
Section: Discussionsupporting
confidence: 50%
“…However, only a few models with objective minimization function are found, highlighting those by Bettinger and Zhu (2006) and Bettinger et al (2014). When properly formulated, minimization models have the potential to ensure stable production flow (FIORENTIN et al, 2017), coupled with low variability in thinning and harvesting operations, which is recommended for operational planning.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy establishment is essential to measure and compare the production performances in the foresttimber industry (Fiorentin et al, 2017). Thereby, trained professionals are required to reach good levels from planning to processing.…”
Section: Introductionmentioning
confidence: 99%
“…Fiorentin et al (2017), por exemplo, tiveram seu trabalho enquadrado na categoria produtiva e a função-objetivo do problema deles era minimizar o desvio da produção entre um ano e o ano seguinte.Ainda queBelavenutti et al (2018) relatem que em certos anos o número significativo de trabalhos incluindo o surgimento de funções-objetivo com caráter não produtivo, como a conservação da biodiversidade e proteção ambiental, esta não é uma realidade brasileira. Apenas dois estudos (4% do total) consideraram tais aspectos.…”
unclassified